MODEL FULL DAY SCHOOL BERBASIS KECERDASAN MAJEMUK UNTUK MENINGKATKAN SPIRITUAL QUOTIENT SISWA DI SEKOLAH DASAR - Muh Luqman Arifin; Adnan Yusufi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
This research was aimed to produce a draft of model full day school to improve the Spiritual Quotient students in elementary school. The method this research used was a Research and Development (R and D) served to develop and validate prototypes. Samples of the research were students of SDIT Al-Ambary, Bumiayu, SDIT Harapan Umat Brebes, and SDTQ Al-Ikhlas, Brebes which implemented full day school system. Data retrieval techniques in this research used a questionnaire methods, observations, tests and interviews. Data retrieval of this research used a product feasibility assessment instruments by the validator and test of spiritual intelligence to students. The results of this research was a teaching book in an effort to improve the spiritual intelligence of students who were worthy of testing based on the assessment of the validator with an average yield of 4.3 or with the predicate "A" very good. And the test results of spiritual intelligence was given to students through the poll technique obtained an average result of 3.5 entering into “good” category.